Stroke risk assessment in patients with persistent atrial fibrillation to consider performing pre-cardioversion transesophageal echocardiography - E. S. Mazur; V. V. Mazur; N. D. Bazhenov; Yu. A. Orlov (Кардиоваскулярная терапия и профилактика)
Aim. To study the potential of stroke risk assessment to evaluate the probability of detecting left atrial appendage (LAA) thrombus in patients with persistent atrial fibrillation (AF) to consider performing transesophageal echocardiography (TEE) before cardioversion.Material and methods. TEE before elective cardioversion was performed in 590 patients with persistent AF, of whom 316 (53,6%) had a high stroke risk (valvular AF, hypertrophic cardiomyopathy, CHA2DS2-VASc score >1 in men and >2 in women), and 274 (46,4%) — not high. Adequate anticoagulation at least 3 weeks prior to elective cardioversion was received by 164 (51,9%) patients with a high stroke risk and 151 (55,1%) patients with a low risk. The rest of patients either did not receive adequate anticoagulation or received it for less than 3 weeks.Results. In the group of patients who received anticoagulation at least 3 weeks, LAA thrombus was detected in 23 (14,0%) patients with a high stroke risk and in 8 (5,3%) patients with a low risk (p<0,05). In patients who did not receive adequate anticoagulation or received it for less than 3 weeks, LAA thrombus was identified in 60 (39,5%) patients with a high stroke risk and in 22 (17,9%) patients with a low risk (p<0,005). Thus, a  high stroke risk almost 3 times increases the likelihood of LAA thrombus detection in patients who did not receive adequate anticoagulation (odds ratio, 2,99; 95% confidence interval: 1,70-5,26;p<0,001) and in patients receiving adequate anticoagulation (odds ratio, 2,92; 95% confidence interval: 1,26-6,74; p=0,012).Conclusion. In patients with persistent AF with a low stroke risk according to CHA2DS2-VASc score, TEE before sinus rhythm restoration in patients without 3-week anticoagulation should be considered. In patients with a high stroke risk, performing pre-cardioversion TEE is advisable even after adequate anticoagulation.